From Local to Global: Examining Indonesian Law Students' Attitudes Towards English Proficiency - Novi Indriyani; Wakerkwa, Dian Agustina Purwanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study investigates the motivations and attitudes towards learning English among law students in Indonesia. Using a quantitative approach, 54 law students from a prominent Indonesian university were surveyed. Descriptive statistics and correlation analyses were employed to examine relationships between motivational factors, attitudes, and self-assessed proficiency. The findings reveal strong instrumental motivation driven by career prospects and academic advancement. While students value English proficiency, a notable gap exists between perceived importance and self-assessed language skills, mainly speaking and listening. Challenges in legal vocabulary acquisition and oral communication were identified as key areas for improvement. The study also found a preference for multimedia and interactive learning methods. These insights provide valuable direction for enhancing legal English education in Indonesia, suggesting a more tailored, interactive, and technology-enhanced approach that addresses law students' specific needs and preferences.